Handling techniques and risk factors reported by veterinary professionals during dog examinations: a cross-sectional survey across Canada and the United States - Nakonechny, Lindsay; Cisneros, Alissa; Moody, Carly M; Stellato, Anastasia Chiara (Frontiers in Veterinary Science, 2025)
IntroductionHandling techniques are known to influence dog stress in veterinary settings; however, little is known about the current handling techniques applied to dogs during routine veterinary care or risk factors associated with their use. This cross-sectional survey aimed to assess common handling techniques used on calm, fearful, and aggressive dogs by veterinary professionals in Canada and the United States and identify risk factors for minimal and full-body restraint.MethodsA convenience sample of veterinary professionals completed an online questionnaire. It collected information on participant characteristics and clinic experience (e.g., gender, Ten Item Personality Index, bite history, stress-reducing certification), participant professional quality of life (using the ProQOL scale), general examination practices (e.g., use of treats), perceptions and importance of examination factors (e.g., staff safety), and frequency of using 14 different dog handling techniques. Logistic regression models were used to identify risk factors for the use of minimal and full-body restraint on fearful and aggressive dogs.ResultsParticipants (N = 691) were veterinarians (39.2%, 271/691) and non-veterinarians (60.8%, 420/691), who routinely handle dogs during routine examinations in Canada (21.7%, 150/691) and the United States (79.1%, 541/691). Minimal restraint was reported to be used for calm (82.7%, 566/684), fearful (73.1%, 499/683), and aggressive (51.9%, 352/678) dogs during routine examinations. Full-body restraint was commonly reported to be used for calm dogs (58.5%, 400/684) and most frequently reported for fearful (63.9%, 434/679) and aggressive dogs (68.6%, 465/678). Handling decisions were influenced by factors including age, gender, practice type, graduation year, bite history, stress-reducing certification, and owner presence. Professionals prioritizing staff safety and using stress-reducing strategies (e.g., treats) were more likely to use minimal restraint, while owner presence and focus on examination completeness were linked to full-body restraint. Personality traits and professional well-being, particularly extraversion and secondary traumatic stress, also influenced handling choices.DiscussionHandling techniques vary with dog behavior and are shaped by numerous factors, highlighting the complex relationship between personal and clinic-level influences on veterinary staff interactions with dog patients. These findings generate hypotheses for future observational research exploring factors that support stress-reducing techniques to improve dog welfare in clinical settings.